Dynamic nuclear magnetic resonance field sensing with part-per-trillion resolution - Gross, Simon (Nat Commun, 2016)
High-field magnets of up to tens of teslas in strength advance applications in physics, chemistry and the life sciences. However, progress in generating such high fields has not been matched by corresponding advances in magnetic field measurement. Based mostly on nuclear magnetic resonance, dynamic high-field magnetometry is currently limited to resolutions in the nanotesla range. Here we report a concerted approach involving tailored materials, magnetostatics and detection electronics to enhance the resolution of nuclear magnetic resonance sensing by three orders of magnitude. The relative sensitivity thus achieved amounts to 1 part per trillion (10(−12)). To exemplify this capability we demonstrate the direct detection and relaxometry of nuclear polarization and real-time recording of dynamic susceptibility effects related to human heart function. Enhanced high-field magnetometry will generally permit a fresh look at magnetic phenomena that scale with field strength. It also promises to facilitate the development and operation of high-field magnets.